Methylphenidate attenuates signs of evoked neuropathic pain in animal model - Panušková, K; Voděrová, L; Vaculín, Š (Physiological research, 2023)
Methylphenidate is a psychostimulant that increases dopamine and noradrenaline levels. Recent studies have shown that methylphenidate potentiates the effect of morphine and together suppress acute and chronic pain. In clinical practice, methylphenidate has been used as a treatment for ADHD and changes of pain threshold have been noted in these patients. The aim of this study was to determine the effect of methylphenidate in an animal model of peripheral neuropathic pain. Neuropathic pain was modeled by the chronic constriction of the sciatic nerve (CCI) in Wistar rats. We evaluated the effect of methylphenidate (1 mg/kg, s.c.) on evoked pain (reflex tests - plantar test, vonFrey test and operant test - thermal place preference) and on spontaneous pain (conditioned place preference). CCI induced thermal, mechanical and cold hyperalgesia/allodynia. Methyphenidate suppressed mechanical and cold hyperalgesia/allodynia, while had no effect on thermal one. Therefore, methylphenidate seems to be a new potential pharmacotherapy for the treatment of neuropathic pain.
Keywords: Animals; Methylphenidate; Disease Models, Animal; lidé; hyperalgezie; Rats; modely nemocí na zvířatech; methylfenidát; neuralgie; Rats, Wistar; Neuralgia; Humans; Hyperalgesia; krysa rodu Rattus; zvířata; potkani Wistar